The Impact of Teaching Medical Law Through Small Group Teaching for Early Clinical Preparedness Among 3rd Professional Part-II MBBS Students - Nandi, Parikshit; Gade, Shubha (Journal of Neonatal Surgery, 2025)
Background: Medical law is a critical aspect of medical education that equips future doctors with the knowledge and skills to navigate medico-legal challenges effectively. Despite its significance, traditional teaching methodologies, primarily lecture-based, limit student engagement and comprehension. Small Group Teaching (SGT) offers an interactive and student-centered approach that bridges the gap between theoretical knowledge and its clinical application. Materials and Methods: This prospective, interventional study will involve pre- and post-intervention assessments. A total of 150 3rd Professional Part-II MBBS students at Gouridevi Institute of Medical Sciences, Durgapur, will be divided into 10 groups of 15 students each. The intervention includes 10 SGT sessions conducted by 4–5 faculty members covering essential medico-legal topics. A structured questionnaire will be administered before and after the sessions to assess knowledge improvement. Feedback will be collected to analyze the effectiveness of SGT in medical law education. Results: The expected outcomes include significant improvement in post-test scores compared to pre-test scores, enhanced clinical preparedness for medico-legal cases, and positive student feedback supporting the integration of SGT into medical law curricula. Conclusion: This study aims to provide empirical evidence on the effectiveness of SGT in teaching medical law, thereby contributing to improved clinical preparedness and patient care among medical students.